Parathyroid hormone receptor stimulation induces human adipocyte lipolysis and browning. Issue 5 (May 2021) - Breining, Peter; Pedersen, Steen B; Kjolby, Mads; Hansen, Jacob B; Jessen, Niels; Richelsen, Bjørn
Abstract : Objective: Activation of brown adipose tissue is a promising strategy to treat and prevent obesity and obesity-related disorders. Activation of uncoupling protein 1 (UCP1) leads to uncoupled respiration and dissipation of stored energy as heat. Induction of UCP1-rich adipocytes in white adipose tissue, a process known as 'browning', serves as an alternative strategy to increase whole body uncoupling capacity. Here, we aim to assess the association between parathyroid hormone (PTH) receptor expression and UCP1 expression in human adipose tissues and to study PTH effects on human white and brown adipocyte lipolysis and UCP1 expression. Design: A descriptive study of human neck adipose tissue biopsies substantiated by an interventional study on human neck-derived adipose tissue cell models. Methods: Thermogenic markers and PTH receptor gene expression are assessed in human neck adipose tissue biopsies and are related to individual health records. PTH-initiated lipolysis and thermogenic gene induction are assessed in cultured human white and brown adipocyte cell models. PTH receptor involvement is investigated by PTH receptor silencing. Results: PTH receptor gene expression correlates with UCP1 gene expression in the deep-neck adipose tissue in humans. In cell models, PTH receptor stimulation increases lipolysis and stimulates gene transcription of multiple thermogenic markers. Silencing of the PTH receptor attenuates the effects of PTH indicating a direct PTH effect via this receptor. Conclusion: PTH 1 receptor stimulation by PTH may play a role in human adipose tissue metabolism by affecting lipolysis and thermogenic capacity.